Work and migration : life and livelihoods in a globalizing world - Sørensen, Ninna Nyberg; Olwig, Karen Fog, 1948- (Transnationalism. Routledge research in transnationalism, 2003)
Using case studies from those who have moved either transnationally or within their own country, international contributions offer various definitions of what it means to make a living on the move.